Back Cover: Use of a solid‐state nanopore for profiling the transferrin receptor protein and distinguishing between transferrin receptor and its ligand protein. Issue 1 (11th January 2023) - O'Donohue, Matthew; Saharia, Jugal; Bandara, Nuwan; Alexandrakis, Georgios; Kim, Min Jun
Abstract : DOI: 10.1002/elps.202200147 The cover picture shows the nanopore‐induced monomerization of a protein dimer. The green and purple proteins are both serum transferrin receptor proteins (TfR). TfR is a dimeric protein, as shown in the far left of the picture. As TfR transits the nanopore, the high electric field (colored arrows) disrupts the secondary interactions of the protein and induces its monomerization. In the right of the picture, each TfR molecule is completely separated and exists in its monomeric form.